A Graphical User Interface (GUI) Based Method for Designing a Mini Hydro-Power - Padmanadhan, Pa. Valar Mathei; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2022)
This research’s study focuses on the creation of a Graphical User Interface (GUI) platform for designing a mini hydro-power plant. The GUI is developed to perform the designing procedure of the mini hydro-power system for Pahang River, Temerloh by considering the parameters of mass flow rate, net head, the efficiency of generator & turbine and penstock size for its desired outputs. This research discusses the proper selection of mini hydro-power plant components such as turbine type, penstock size, and net head length, which are the major components of the power station. The results obtained for the design of the mini hydro-power plant for Pahang River, Temerloh with a flow rate of 38.53 m3/sec are as follows. The penstock length, penstock diameter, penstock minimum wall thickness and net head are 10m, 2230mm, 6.854mm and 3.24m respectively. The PVC was chosen as the penstock pipe material and the suitable turbine was Kaplan which is a reaction type. The mini hydro-power plant is a renewable energy plant that offers several benefits over wind and solar renewable energy plants of the same size. Hydro-power is completely pure, therefore it will never run out until the water supply is cut off, the power generation emits no pollution into the atmosphere, and it is the most dependable renewable energy source known. The developed GUI was able to identify the specifications of all the components that were to be utilized to create a mini hydro-power system. The GUI application was able to generate the same result as the manually computed design specifications.